Criação e captura de valor no modelo de negócios dos escritórios digitais bancários - Brunelli, Tiago da Silva (2020)
The internet and the digital environment have brought, in recent years, several opportunities. With the advancement of these technologies, traditional business models have been transformed, allowing to explore different channels, providing new services and new information, in a personalized way, changes in business models. In this context, traditional retailers, such as banks, are struggling to survive. When you look more closely, you see that these companies have the same challenge: to develop new business models that work in the global digital environment and create value for customers. In other cases, new business models emerge. This study aims to examine how value creation and capture occurs in the business models of digital offices and bank branches, using high-income customer service. The study was carried out in three banking units in Curitiba (PR), in the period from November to December 2019. Searches carried out on the topic in the main national academic databases, identified as the existence of a study gap with the same purpose, destined to the banking and high-income segments. To answer the question and the research objectives, adopt the qualitative method, under an interpretive perspective. A typology of study characterized as an exploratory and descriptive case study, within an abductive logic. Data collection was carried out through semi-structured interviews (recorded and transcribed), with 16 managers working in high-income banking services. For data treatment and interpretation, use the NVivo® 12 Plus software, in order to create and organize categories (or "nodes"), or the basic service to analyze the contents of the interviews, in accordance with the objectives used. study. The results demonstrated the relationship managers' adequate awareness of the innovation provided in the Business Model, as well as the elements for creating and capturing value. Therefore, using the theoretical framework, data collection and analysis and interpretation of information, the present research suggests a Framework called “Elements of creation and capture of value in the Business Models Innovation in the banking sector”, contemplating the elements creating value: (i) agility and ease, (ii) relationship and personality, (iii) serving remote areas, (iv) simplifying tasks, (v) meeting market needs, (vi) personalizing service in depending on the age of the client, (vii) benefit to society as a whole and (viii) investment in marketing and value capture: (i) cost reduction and (ii) increase in profit.